Routine Activity Theory and the Likelihood of Arrest: a Replication and Extension With Conjunctive Methods: - Drawve, Grant R. (Journal of contemporary criminal justice, 2017)
Drawve, Thomas, and Walker applied routine activity theory (RAT) to examine whether measures of offender motivation, target suitability, and guardianship influence the likelihood of an offender’s arrest in incidents of aggravated assault. The current study uses the method of conjunctive analysis of case configurations (CACC) to explore the robustness of their results across alternative analytic methods. We begin with an estimation of the basic “main-effect” model used in the original article and then perform a series of conjunctive analyses to evaluate the contextual variability within each variable in this model. The observed pattern of substantial context-specific effects in the conjunctive analysis illustrates the limitation of traditional quantitative analysis and the utility of CACC for future exploratory and confirmatory studies in evaluating RAT and other criminological research questions.